Basic finger inner‐knuckle print: A new hand biometric modality - Farah Bahmed; Madani Ould Mammar (IET Biometrics)
Abstract In this study, a new accurate hand biometric modality for person authentication is proposed. This modality consists in the basis of the finger, which is located below the proximal knuckle and above the metacarpo knuckle of the finger, and which was not investigated yet in the literature. A multimodal biometric system which uses a new combination of metacarpo and distal phalanx is also designed and tested. Additionally, an improved features extraction method called Average Line Local Binary Pattern (ALLBP), is introduced to improve features extraction of this region of the inner print of the finger. Experimental tests on a standard database show very good performance of the basic Inner‐knuckle print for biometric recognition using ALLBP, and the high accuracy of the proposed hand bimodal system.